Review of Various SEO Techniques for Websites - Singh, Manraj; Singh, Harmanjit (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Advancement of e-commerce which includes buying and selling of products or services over the Internet has revolutionized the way a Business is done. Now consumers are becoming more comfortable buying and selling products over Internet rather than in a physical market(s). This new trend has started a cut throat competition among the websites of various business owners. There was a time when every businessman required a descent looking website and that’s it, nothing else was required. But now things have changed. Now a businessman not only requires a good looking user friendly website, but also needs to get Website(s) optimized for search engines also. This is a review paper on the various SEO Techniques that can be used by webmasters to improve website’s visibility in search results and improve traffic to the website.